ARCHITECTING SERVERLESS PAYMENT GATEWAYS: A SYSTEMATIC ANALYSIS OF SCALE, SECURITY, AND PERFORMANCE TRADE-OFFS - Bharath Kumar Reddy Janumpally (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article presents a comprehensive analysis of serverless computing architecture for modern payment gateway systems, addressing the challenges of scalability, security, and cost-efficiency in financial transaction processing. We propose a novel architectural framework that leverages event-driven serverless functions for core payment operations while maintaining compliance with industry standards. The architecture incorporates mechanisms for handling cold start latency, managing distributed state, and ensuring transaction consistency in a stateless environment. The implementation demonstrates how serverless components can be effectively orchestrated to process payment transactions while meeting strict security requirements and maintaining performance under variable load conditions. Through extensive performance evaluation and a real-world case study, we show that the proposed architecture achieves significant improvements in scalability and cost-efficiency compared to traditional payment gateway implementations, while successfully addressing key challenges in areas such as fraud detection and compliance. The findings suggest that serverless architectures, when properly implemented with appropriate optimization strategies, offer a viable solution for building robust, scalable payment gateway systems that can effectively handle modern transaction processing requirements.